The barriers and accessibility of Klang Valley residents in accessing healthcare - Redzuan Teo, Inss Emelda Teo; James, Christabelle Jemin; Zhi, Bong Lai; Shing, Liau Ling; Yasin, Yusma Fariza (Journal of Islamic, Social, Economics and Development, 2025)
This research examines the barriers and accessibility challenges faced by Klang Valley residents in accessing healthcare services. With a growing population and diverse socioeconomic groups, the Klang Valley presents a unique case for exploring how healthcare accessibility is influenced by factors such as geographic location, affordability, availability of healthcare professionals, and insurance coverage through online questionnaires. The study identifies key obstacles such as long waiting times, high out-of-pocket expenses, limited healthcare coverage, and transportation issues, which affect residents' ability to obtain timely medical care. Through survey data and analysis, this research reveals the significant role of digital health solutions, including mobile health applications, in improving access to healthcare, especially during the COVID-19 pandemic. The findings underscore the importance of expanding healthcare infrastructure, increasing the availability of healthcare personnel, and implementing cost-effective strategies to address these barriers. By addressing these issues, the research aims to provide recommendations for policymakers and healthcare providers to enhance the accessibility and quality of healthcare services in urban areas like Klang Valley.